Neoliberalism and the Mutations of Social Realism in Contemporary European Cinema (Cinéma & Cie. Film and Media Studies Journal, 2024)
Over the last couple of decades film scholars have begun building a critical vocabulary to theorize the new kinds of social relations depicted in the new European cinema of precarity, from “flexible solidarity” and “precarious intimacies” to “the gift economy” and “cruel optimism”. Although the European cinema of precarity continues the legacy of older film traditions like French poetic realism, Italian neorealism and British kitchen sink realism, thus inscribing itself within a well-established European tradition of social realism, the realism of precarity films is often refracted through specific genre tropes or filmic devices—e.g., allegory, experimental cinema techniques, black comedy, cinema verité cinematography etc.—as though social realism is no longer able to render visual the hidden pathologies of neoliberalism or to capture the complexity of Europe’s current political, economic, and moral crisis.
Keywords: Precarity; European Cinema; Social Realism; Work; Genre